LES EFFETS DES PROGRAMMES D'ETE DE LITTERATIE: LES THEORIES SUR LES OPPORTUNITES D'APPRENTISSAGE ET LES ELEVES << NON TRADITIONNELS >> DANS LES ECOLES DE LANGUE FRANCAISE EN ONTARIO - Davies, Scott; Aurini, Janice; Milne, Emily; Jean-Pierre, Johanne (Canadian journal of sociology, 2015)
According to studies from the United States and English Canada, student achievement gaps grow over the summer months when children are not attending school, but summer literacy interventions can reduce those gaps. This paper presents data from a quasi-experiment conducted in eight Ontario French language school boards in 2010, 2011 and 2012 for 682 children in grades 1-3. Growth in literacy test scores between June and September are compared for 361 attendees of summer literacy programs and 321 control students. Summer program recruits initially had lower prior literacy scores and grades, and tended to hail from relatively disadvantaged social backgrounds. Yet, summer programs narrowed those pre-existing gaps. Effect sizes from a variety of regression and propensity score matching models ranged from .32 to .58, which is quite sizeable by the standards of elementary school interventions and summer programs. Effects were stronger among students whose parents reported not speaking French exclusively at home. Our paper considers learning opportunity theory in light of the "non-traditional" student in Ontario French language schools.